2016
DOI: 10.1038/nature18309
|View full text |Cite
|
Sign up to set email alerts
|

Acetate mediates a microbiome–brain–β-cell axis to promote metabolic syndrome

Abstract: Obesity, insulin resistance and the metabolic syndrome are associated with changes to the gut microbiota; however, the mechanism by which modifications to the gut microbiota might lead to these conditions is unknown. Here we show that increased production of acetate by an altered gut microbiota leads to activation of the parasympathetic nervous system which in turn promotes increased glucose-stimulated insulin secretion (GSIS), increased ghrelin secretion, hyperphagia, obesity and its related sequelae (Extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
791
5
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,080 publications
(849 citation statements)
references
References 24 publications
35
791
5
18
Order By: Relevance
“…Infusion of acetate, but not butyrate or propionate, in chowfed rats mimicked increased GSIS as observed in HFD-fed rats suggesting that circulating acetate levels drive increased GSIS [4]. In line with this, FMT from HFD-fed rats to chow-fed controls increased acetate turnover and GSIS in the recipient rat.…”
Section: Role Of Specific Bacterial Metabolites In Regulation Of Hostsupporting
confidence: 63%
See 2 more Smart Citations
“…Infusion of acetate, but not butyrate or propionate, in chowfed rats mimicked increased GSIS as observed in HFD-fed rats suggesting that circulating acetate levels drive increased GSIS [4]. In line with this, FMT from HFD-fed rats to chow-fed controls increased acetate turnover and GSIS in the recipient rat.…”
Section: Role Of Specific Bacterial Metabolites In Regulation Of Hostsupporting
confidence: 63%
“…Perry and co-workers recently showed that the SCFA acetate acts on parasympathetic activity to increase food intake and promote glucose-stimulated insulin secretion (GSIS) in a rat model [4]. Interestingly, acetate turnover, but not that of butyrate or propionate, was found to be increased in the colon, caecum and brain of rats fed an HFD compared with chow-fed rats.…”
Section: Role Of Specific Bacterial Metabolites In Regulation Of Hostmentioning
confidence: 96%
See 1 more Smart Citation
“…Specific microbiome profiles are associated with increased glucose intolerance [30]. Alterations in gut microbiota can influence the gut metabolome in a manner that affects the intestinal output of butyrate [24] and acetate [31]. These are important examples of gut-derived metabolites that can influence host insulin resistance, and thus glycaemic control.…”
Section: Metformin and Gut Microbiotamentioning
confidence: 99%
“…In normal mice with normal gut microbiota, inactive AMPK is associated with decreased FA oxidation in skeletal muscle (36). In addition, gut satiety hormones are affected by the gut microbiome through the gut-brain axis (65). Therefore, the gut microbiome influences energy intake in addition to energy expenditure.…”
Section: Introductionmentioning
confidence: 99%